Appropriate Diagnostic Approach in Patients with Suspicious Bone Metastasis from Low FDG-Avid Primary site in Thyroid gland: Case report - Akhter, Afroza; Jeon, Subin; Bom, Hee Seung; Min, Jung Joon; Kwon, Seong Young (Bangladesh Journal of Nuclear Medicine, 2022)
Metastatic bone tumors are the most common malignant tumor involving bone. Bone metastases from primary tumors of unknown origin are commonly attributed to prostate, breast, lung, and thyroid. 18F-fluorodeoxyglucose (FDG) Positron Emission Tomography- Computed Tomography (PET-CT) has a very useful imaging modality to identify primary site in patients with suspicious bone metastasis. However, it remained unclear whether PET-CT have clinical value to identify primary site because some cancer types have low FDG-avidity. We report a case of 84-year-old female patient presenting with metastatic bone tumor in skull without showing any metabolic activity in primary site of her thyroid gland on FDG PET-CT and we discussed how to use other clinical information in this patient. Bangladesh J. Nuclear Med. 23(1&2): 63-66, 2020